Transplante interespecífico de espermatogônias-tronco de Brycon orbignyanus em Astyanax altiparanae (Teleostei: Characidae) - Silva, Diógenes Henrique de Siqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Germ cell transplantation is a recent approach which involves removal of undifferentiated germ cells from the donor gonads and transplantation into the gonads of a host, giving origin to sperm with genetic characteristics from the donor. Despite this methodology promising in studies involving initial germ cell biology, preservation of threatened species, reproductive biology and many other biotechnological approaches, the application of such a methodology in fish is still limited. Thus, the transplantation of spermatogonial cells from two phylogenetically related species piracanjuba Brycon orbignyanus into lambaris Astyanax altiparanae testis was histologically studied. Host spermatogenesis and urogenital papilla (transplantation via) were analyzed, highlighting nine spermatogonial generations and that each Sertoli cell supports the development of about 140 spermatids. Moreover, urogenital papilla is different between the sexes. For transplantation, piracanjuba's testes were enzymatic digested and spermatogonia were purified by a density gradient (Percoll), labeled with PKH26 and injected, through urogenital papilla, into lambaris testes, whose endogenous spermatogenesis had been previously suppressed by administration ofbusulfan (Myleran) associated with warm water (35°C) or by their maintenance at this temperature for longer time. About 66.67% and 84.6% of the host animals treated with busulfan + temperature and only temperature, respectively, presented cysts of donor germ cells into their epithelium. Spermatogonial transplantation involving B. orbignyanus and A. altiparanae was successfully performed and it can be applied in fish farms helping production increase and preservation of donor species piracanjuba (critically endangered), since donor spermatozoon can be obtained up to three weeks after transplantation process.

O transplante de células germinativas é uma recente abordagem experimental que envolve a remoção de células germinativas indiferenciadas das gônadas de um animal doador, e transplante nas gônadas de um receptor originando espermatozoides com características genéticas do doador. Apesar de ser promissora em estudos que envolvem a biologia das células germinativas iniciais, preservação de espécies ameaçadas, biologia da reprodução e muitas outras abordagens biotecnológicas, a aplicação desta metodologia em peixes ainda é limitada. Deste modo, o transplante de células espermatogoniais de duas espécies filogeneticamente relacionadas, a piracanjuba Brycon orbignyanus em lambaris Astyanax altiparanae foi estudada. Para isto, a espermatogênese e a papila urogenital (via do transplante) da espécie receptora foram histologicamente analisadas, evidenciando a presença de nove gerações espermatogoniais e que a cada célula de Sertoli suporta o desenvolvimento de cerca de 140 espermátides. Além disso, a papila urogenital difere entre os sexos. Para o transplante, os testículos das piracanjuba foram enzimaticamente digeridos e as espermatogônias foram purificadas por um gradiente de densidade (Percoll), marcadas com PKH26, e injetadas, via papila urogenital, nos testículos dos lambaris, cuja espermatogênese endógena foi previamente suprimida por administração de busulfan (Myleran) associado com água quente (35°C) ou por sua manutenção nesta temperatura por um período maior. Cerca de 66,7% e 84,6% dos receptores tratados com busulfan + temperatura e somente temperatura, respectivamente, apresentaram cistos de células germinativas doadoras em seu epitélio. O transplante espermatogonial envolvendo B. orbignyanus e A. altiparanae foi realizado com sucesso e pode ser aplicado em pisciculturas auxiliando no aumento da produção e preservação da piracanjuba (criticamente ameaçada de e
Keywords: Citologia; Peixe de agua doce - Reprodução; Espermatogenese em animais; Celulas germinativas; Celulas - Separação; Quimerismo